Correlación del funcionamiento ejecutivo y la potencia absoluta del EEG en niños. - Galicia-Alvarado, Marlene; Flores-Ávalos, Blanca; Sánchez-Quezada, Ana; Yáñez-Suárez, Óscar; Brust-Carmona, Héctor (Salud Mental)
Introduction: The resting EEG power is considered as a robust marker of brain function; however, a few studies have associated it to a specific function. Objective: To analyze the relationship between EEG absolute power (AP) with performance on tasks of executive functioning in children. Method: Correlational cross-sectional study of 30 children (8.6 ± 1 year). EEG was performed with eyes closed and bipolar leads. With the Fourier transform AP was calculated in the spectrum of 1.6, 30 Hz. NEUROPSI Attention and Memory was applied and the Index of Attention and Executive functions (IAFE) was calculated. Based on this, the AP was compared with Kruskal-Wallis and the Z value, Spearman coefficient for correlation with the subtests. Results: Children with severe impairment (? = 63 ± 8 CI 95% [57.2, 68.5]) had higher delta AP (a = .05) in F1F7, P301 and P402, and Z values near 2 SD in F7T3, F3C3 and F8T4 at slow frequencies. Correlations were significant between the IAFE and delta AP P301 (-.57), P402 (-.43) and T5O1 (-.37); with AP alpha mainly on left fronto-temporo - parietal-occipital areas. The score in Visual Detection and Semantic Fluency inversely related to AP alpha frequency. Discussion and conclusion: Performance on tasks of executive functioning is different in relation to the frontal and parietal AP delta. There is an inverse relationship between AP delta and alpha at rest with attention and verbal fluency.